2016
DOI: 10.1159/000441191
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Methylation and CpG Single-Nucleotide Polymorphisms in the HTR2A Gene: Association Analysis with Suicide Attempt in Schizophrenia

Abstract: Dysfunctional mechanisms in the serotonergic system have been implicated in suicidal behavior among patients with schizophrenia. However, previous association analyses of major serotonin genes have provided inconsistent findings regarding their role in suicidal behavior. The goal of the current study was to identify single-nucleotide polymorphisms (SNP) within HTR2A that directly affect CpG methylation sites in schizophrenic patients with suicidal behavior. Furthermore, direct methylation analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…Although many of these SNPs overlapped with pre‐mRNA processing sites, Piva et al () suggested that they do not affect transcript processing due to redundancy of signal sites that complement each other. Furthermore, experimental data shows that SNPs, methylation, and expression changes of HTR2A are associated with risk for SZ, suicidal behavior in patients with SZ, and tardive dyskinesia, a common side effect of treatment (Bani‐Fatemi et al, ; Castensson et al, ; Zhang et al, ).…”
Section: Serotonin Pathway Genes Associated With Szmentioning
confidence: 99%
“…Although many of these SNPs overlapped with pre‐mRNA processing sites, Piva et al () suggested that they do not affect transcript processing due to redundancy of signal sites that complement each other. Furthermore, experimental data shows that SNPs, methylation, and expression changes of HTR2A are associated with risk for SZ, suicidal behavior in patients with SZ, and tardive dyskinesia, a common side effect of treatment (Bani‐Fatemi et al, ; Castensson et al, ; Zhang et al, ).…”
Section: Serotonin Pathway Genes Associated With Szmentioning
confidence: 99%
“…However, in a recent report Bani-Fatemi and group attempted to find out a functional link between hyposerotonergic neurotransmission and 25 methylated polymorphic loci of HTR2A gene in blood genomic DNA of 32 suicide attempters with major psychosis (Bani-Fatemi et al, 2016). Though the study was unable to establish a possible connection between the 5HT based epigenetic changes and suicide risk in schizophrenia patients but was able to determine significant hypermethylation at a genetically variable locus (rs6313) in the exon I of HTR2A gene.…”
Section: Future Directionsmentioning
confidence: 99%
“…There are an increasing number of laboratory experiments that provide evidence of DNA methylation and gene expression regulation [ 3 5 ]. Only a few studies, however, have evaluated the genome–epigenome interactions through statistical means, which may potentially provide novel findings for the joint effects of SNPs and cytosine-phosphate-guanine (CpG) sites [ 6 9 ]. The search for SNP-CpG epistasis is usually conducted through multistage or integrated analyses, where the genome and methylation data are first analyzed separately and the results then combined [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%